Influence of heat treatment in vacuum on shungite shielding properties - E. S. Belousova; L. M. Lynkou; V. T. Senyut’; E. A. Krishtopova (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
The research results of structure, chemical composition, reflection and transmission coefficients of powder shungite after heat treatment at 900 °С for 2 h are presented. According X-ray diffraction study, orthoclase was formed, modifications of carbon saved. Transmission coefficient increased in 12 dB in the range 8-12 GHz.